P012 The effect of Oncostatin M on human intestinal organoids. (21st January 2022) - Filidou, E; Kandilogiannakis, L; Kokkotis, G; Tarapatzi, G; Arvanitidis, K; Drygiannakis, I; Valatas, V; Paspaliaris, V; Kolios, G; Bamias, G
Abstract: Background: We have previously shown that human subepithelial myofibroblasts (SEMFs), which are of mesenchymal origin, express the receptor of Oncostatin M (OSM), which is further induced when SEMFs are previously exposed to IL-1α and TNF-α. Human Intestinal Organoids (HIOs), derived from embryonic stem cells (ESC), form epithelial crypts consisting of several subtypes of epithelial cells and are surrounded by cells of mesenchymal origin. Recently, we reported that the mesenchymal component of HIOs is gradually reduced, as culture passages increase. The aim of our study was to examine the effect of exogenous OSM on fibrotic and pro-inflammatory marker expression of HIOs, with and without the combined presence of IL-1α and TNF-α. Methods: The human ESC line (H1)-derived HIOs were developed using a commercially available kit and characterized by immunofluorescence in all differentiation stages. HIOs from passage 2 were stimulated with either 100ng/ml OSM for 12 hours or 5ng/ml IL-1α and 50ng/ml TNF-α for 24 hours and then with 100ng/ml OSM for 12 hours. mRNA expression of fibrotic markers, Collagen Type I, III, and Fibronectin, and pro-inflammatory markers, CCL2, CXCL10 and CXCL11 were examined by reverse transcription quantitative PCR. Results: OSM alone significantly downregulated both Collagen Type I and III mRNA expression, and had no effect on Fibronectin expression. When HIOs were previously exposed to IL-1α and TNF-α, however, OSM stimulation resulted in significant upregulation of Collagen Type I and Fibronectin, and had no effect on Collagen Type III. Regarding the pro-inflammatory marker expression, OSM alone induced the expression of CCL2, CXCL10 and CXCL11, with a greater effect observed when HIOs were previously exposed to IL-1α and TNF-α. Conclusion: Our findings indicate that OSM induces the expression of both fibrotic and pro-inflammatory factors in early passages of HIOs, previously exposed to IL-1a and TNF-a, as has been previously observed on SEMFs. Since the mesenchymal cell component of HIOs is strongly present in early passages and OSM's receptor is mainly found to be expressed in these cells, our results suggest OSM affects HIOs via the cells that are of mesenchymal origin.